Electronic Record Linkage cohort study of evidence-based management and outcomes in patients with ischaemic heart disease and atrial fibrillation - EDWARD HARRIS (2021)
BACKGROUND Implementation of evidence-based medicine is often suboptimal. The objectives of this thesis are to explore the delivery of evidence-based medicine and outcomes in patients with ischaemic heart disease (IHD) and atrial fibrillation (AF). METHODS Retrospective observational cohort studies were conducted using linked anonymised data from the secure anonymised information linkage (SAIL) databank. Patients included (i) those undergoing percutaneous coronary intervention, (ii) patients prescribed vitamin K antagonist (VKA) for AF, and (iii) patients with AF who had undergone successful PCI. RESULTS Amongst patients directed to take clopidogrel for one-year post-PCI, discontinuation was far lower (~6%) than in previous studies where the treatment duration was not known. Despite this, early discontinuation and/or bleeding was associated with an increased risk of adverse events. In a national cohort of PCI patients, we observed a low rate of achievement of international guideline target lipid levels (<25%) and low prescribing of intensive lipid lowering therapy amongst those not at target. Females and patients who had undergone elective PCI were least likely to have their lipid levels documented and be at target. In patients prescribed VKA for AF guideline defined poor anticoagulation control was common and associated with significantly higher bleeding event rates, independent of common comorbidities that are recognised as risk factors for stroke and bleeding. In patients with AF who had undergone PCI outcomes were poor: approximately 1 in 5 had either a stroke, acute coronary syndrome (ACS) or died in the year follow-up. Bleeding events were also common and associated with a five, three and four-fold increased risk of stroke, ACS, and death. CONCLUSION This thesis has characterised the nature of multiple therapeutic gaps and associated adverse outcomes with common clinical conditions. Thus, identifying opportunities to improve outcomes in individual patients and at population level.